Innovative School Leadership and Digital Literacy of Islamic Education Teachers - Rohani Rohani; Yuniar Yuniar; Mardiah Astuti; Ahmad Zainuri (Journal of General Education and Humanities, 2026)
The rapid technological shift in education increasingly requires teachers to demonstrate strong digital literacy aligned with continuous curriculum reform processes. In Indonesia, the Merdeka Curriculum promotes learner-centred pedagogy and systematic technology integration; however, many Islamic Education teachers still struggle to effectively apply digital competencies in lesson planning, instructional delivery, and assessment practices. This qualitative case study examined how innovative school leadership supports and strengthens teachers’ digital literacy development in a public secondary school in South Sumatra. Data were collected through semi-structured interviews, non-participant classroom observations, and document analysis involving principals, teachers, administrative staff, and students. The data were analysed thematically using iterative analytical procedures supported by trustworthiness strategies. The findings reveal that leadership practices such as shared vision building, mentoring, instructional supervision, and collaborative professional learning consistently embed digital competence within school planning and ongoing professional development. These practices enhance teachers’ confidence, adaptability, and their use of digital tools in the classroom. Overall, leadership bridges curriculum reform objectives with teachers’ digital readiness in Education contexts.